Finding the Best Fe 2+/Cu 2+ Combination for the Solar Photoelectro-Fenton Treatment of Simulated Wastewater Containing the Industrial Textile Dye Disperse Blue 3 - Salazar-Gonzalez, R (2012)
The performance of the solar photoelectro-Fenton (SPEF) process with Fe 2+ and Cu 2+ as metal co-catalysts and its application to the treatment of solutions simulating Disperse Blue 3 (DB3) dye bath effluents of a Chilean textile company are reported in this paper. The trials were carried out with 2.5l solutions using a solar pre-pilot plant containing an electrochemical reactor with a 20cm 2 BDD anode and air-diffusion cathode, coupled to a 600ml solar photoreactor. DB3 solutions with 0.1M Na 2SO 4 at pH 3.0 were electrolyzed to assess the effect of the applied current density, catalyst nature and concentration and dye content on the decolorization rate, dye removal and total organic carbon (TOC) abatement. The SPEF treatments using 0.5mM Fe 2++0.1mM Cu 2+ led to the quickest degradation kinetics, mainly due to the concomitant action of UV photolysis and the generated oxidizing hydroxyl radicals on the organic molecules and/or their Cu(II) and Fe(III) complexes. Based on the identification of up to 15 aromatic by-products by GC-MS, a reaction scheme for DB3 degradation has been proposed. The progressive color and TOC removal of DB3 solutions were due to various changes undergone by the initial anthraquinonic structure, including the modification/addition of auxochromes giving 6 anthraquinonic by-products and its cleavage to yield compounds with 2 aromatic rings due to intermolecular cyclization or 1 aromatic ring mainly in the form of phthalic acid derivatives. Upon cleavage of these aromatics, maleic, oxalic, oxamic, pyruvic and acetic acids were formed. NO 3 - ions were released to a larger extent than NH 4 + ions. The great efficacy of SPEF with Fe 2+ and Cu 2+ was demonstrated for simulated wastewater containing DB3 and industrial surfactants and additives at 50mAcm -2, allowing their total decolorization and almost overall mineralization in only 150 and 360min, with an energy consumption of 11.0 and 26.4kWhm -3, respectively. © 2011 Elsevier B.V..